“Je Cherche La Vie!”: Women's Labour Politics in Masisi's Artisanal Coltan Mines - Furniss, Allison (Department of Political Studies, 2021)
In considering how women navigate the complexity and gendered aspects of the artisanal mining industry, this study seeks to unpack women's labour at step one of the global supply chain of coltan, in the post-conflict context of eastern Democratic Republic of Congo (DRC). Female miners are largely excluded from mine work by blurry regulatory frameworks, gendered social norms and financial disparities, however they manage to remain active labourers in the artisanal mining industry. Within a broader socio-political context of poverty, political instability and rural livelihoods, women maintain access to mine work through strategies, often premised on a gendered solidarity, such as organizing into collectives, engaging in small group collaborations and employing creative ruses to maintain the secrecy of their labour. This thesis seeks to analyze women's exclusions from mine work and the subsequent strategies they employ to circumvent those exclusions and maintain work in the mines. Based on three months of ethnographic fieldwork at artisanal coltan mine sites in Masisi Territory in the province of North Kivu, this study employs ethnographic observations, focus group and interview methodologies.